A new type of pharmacological chaperone for GM1-gangliosidosis related human lysosomal β-galactosidase: N-Substituted 5-amino-1-hydroxymethyl-cyclopentanetriols. Issue 15 (1st August 2017) - Schalli, Michael; Weber, Patrick; Tysoe, Christina; Pabst, Bettina M.; Thonhofer, Martin; Paschke, Eduard; Stütz, Arnold E.; Tschernutter, Marion; Windischhofer, Werner; Withers, Stephen G.
Graphical abstract: Highlights: A short and high yielding route enables access to N -substituted amino(hydroxymethyl)pentanetriols. Final products are potent inhibitors of a panel of β-galactosidases. New compounds are efficient pharmacological chaperones for GM1 -gangliosidosis-related human lysosomal β-galactosidase. Abstract: N -Functionalized amino(hydroxymethyl)cyclopentanetriols are potent inhibitors of β-d -galactosidases and, for the first time, could be shown to act as pharmacological chaperones for GM1 -gangliosidosis-associated lysosomal acid β-galactosidase thus representing a new structural type of pharmacological chaperones for this lysosomal storage disease.